The effectiveness of an additive informal social network intervention for forensic psychiatric outpatients: results of a randomized controlled trial - Swinkels, Lise T. A.; van der Pol, Thimo M.; Twisk, Jos; ter Harmsel, Janna F.; Dekker, Jack J. M.; Popma, Arne (Frontiers in Psychiatry, 2023)
Objectives: A supportive social network is associated with better mental health and wellbeing, and less criminal behavior. Therefore, this study examined the effectiveness of an additive informal social network intervention to treatment as usual (TAU) among forensic psychiatric outpatients. Materials and methods: An randomized controlled trial (RCT) was conducted in forensic psychiatric care, allocating eligible outpatients (N = 102) to TAU with an additive informal social network intervention or TAU alone. Participants receiving the additive intervention were matched to a trained community volunteer over 12 months. TAU consisted of forensic care (e.g., cognitive behavioral therapy and/or forensic flexible assertive community treatment). Follow-up assessments were conducted at 3, 6, 9, 12, and 18 months after baseline. The primary outcome was the between-group effect on mental wellbeing at 12 months. Between-group effects on secondary outcomes (e.g., general psychiatric functioning, hospitalization, criminal behavior) were explored. Results: Intention-to-treat analyses showed non-significant between-group effects on mental wellbeing on average over time and at 12 months. However, significant between-group effects were found on hospitalization duration and criminal behavior. Specifically, TAU participants were hospitalized 2.1 times more days within 12 months and 4.1 more days within 18 months than participants in the additive intervention. Furthermore, TAU participants reported 2.9 times more criminal behaviors on average over time. There were no significant effects on other outcomes. Exploratory analyses revealed that sex, comorbidity, and substance use disorders moderated effects. Conclusion: This is the first RCT examining the effectiveness of an additive informal social network intervention in forensic psychiatric outpatients. Although no improvements were found on mental wellbeing, the additive intervention was effective in reducing hospitalization and criminal behavior. The findings suggest that forensic outpatient treatment can be optimized by collaborating with informal care initiatives aimed at improving social networks within the community. Future research is warranted to determine which specific patients might benefit from the intervention and if effects can be improved by extending the intervention duration and enhancing patient compliance. Clinical trial registration: [https://trialsearch.who.int/Trial2.aspx?TrialID=NTR7163], identifier [NTR7163].